Raman spectroscopy on mechanically exfoliated pristine graphene ribbons. Issue 12 (21st October 2014) - Terrés, Bernat; Reichardt, Sven; Neumann, Christoph; Watanabe, Kenji; Taniguchi, Takashi; Stampfer, Christoph
<x xml:space="preserve">Abstract</x> We present Raman spectroscopy measurements of non‐etched graphene nanoribbons, with widths ranging from 15 to 160 nm, where the D‐line intensity is strongly dependent on the polarization direction of the incident light. The extracted edge disorder correlation length is approximately one order of magnitude larger than on previously reported graphene ribbons fabricated by reactive ion etching techniques. This suggests a more regular crystallographic orientation of the non‐etched graphene ribbons here presented. We further report on the ribbons width dependence of the line‐width and frequency of the long‐wavelength optical phonon mode (G‐line) and the 2D‐line in the studied graphene ribbons. <inline-graphic xlink:href="ark:/27927/pgh2jcbgb7w" content-type="pssb201451398-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Scanning force microscope image of graphene ribbons on hexagonal boron nitride and SiO<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbg4c0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives> substrates. The scale bar is 1<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbg4jr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μ</alternatives>m.